2(x-6)-6(x-2)=x+5-(x-11)

Simple and best practice solution for 2(x-6)-6(x-2)=x+5-(x-11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-6)-6(x-2)=x+5-(x-11) equation:


Simplifying
2(x + -6) + -6(x + -2) = x + 5 + -1(x + -11)

Reorder the terms:
2(-6 + x) + -6(x + -2) = x + 5 + -1(x + -11)
(-6 * 2 + x * 2) + -6(x + -2) = x + 5 + -1(x + -11)
(-12 + 2x) + -6(x + -2) = x + 5 + -1(x + -11)

Reorder the terms:
-12 + 2x + -6(-2 + x) = x + 5 + -1(x + -11)
-12 + 2x + (-2 * -6 + x * -6) = x + 5 + -1(x + -11)
-12 + 2x + (12 + -6x) = x + 5 + -1(x + -11)

Reorder the terms:
-12 + 12 + 2x + -6x = x + 5 + -1(x + -11)

Combine like terms: -12 + 12 = 0
0 + 2x + -6x = x + 5 + -1(x + -11)
2x + -6x = x + 5 + -1(x + -11)

Combine like terms: 2x + -6x = -4x
-4x = x + 5 + -1(x + -11)

Reorder the terms:
-4x = x + 5 + -1(-11 + x)
-4x = x + 5 + (-11 * -1 + x * -1)
-4x = x + 5 + (11 + -1x)

Reorder the terms:
-4x = 5 + 11 + x + -1x

Combine like terms: 5 + 11 = 16
-4x = 16 + x + -1x

Combine like terms: x + -1x = 0
-4x = 16 + 0
-4x = 16

Solving
-4x = 16

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-4'.
x = -4

Simplifying
x = -4

See similar equations:

| -2x+13=10-2x | | -9=x+(-19) | | 7y-2=19y+82 | | 10x-(6x-5)=41 | | 4x+5=2x+1 | | 2(2-3n)=[5n-(4-n)] | | x/3*8=3 | | 3m+8m=9m+m | | 3(2x-1)+4(x+3)=5(2-1)+4(3x-1) | | 3x*6=48 | | 2x=32-x | | 3(x-3)=7(x-2)-3 | | 2x-3(x-4)=8x-(5x-3) | | 2x^2-14x+9=0 | | +6v-v=7 | | x^2+6=11x | | -8x+4+2x=-10x+24 | | -n-5n=12 | | 2(2x+5)+5(x-7)= | | -10y+5=-5(2y-1) | | 2(2x-1)-6(1-2x)=2(4x-5) | | X^4-81=o | | 2(1-5x)=(5x-1) | | x-4+2=3 | | z/4-z/3-z/8=2 | | 3n-5+4n=16 | | -2m+6+6=16 | | 448=-16p | | 12x-9x^2=3 | | 36x^2-48x+16=0 | | 6-3= | | 6x^3-3x^2-2x+1=0 |

Equations solver categories